Back side pad bonding of hard disk head slider - Kamano,K. (Chiang Mai University, 2015)
In the magnetic head of disk drive, the head slider is the major and lucrative part. Therefore, to increase the efficiency and serve an exponential growth of Hard Disk Drive industry, there is a need to continuously improve the slider. An approach to enhance the slider efficiency is to increase the number of sensors, leading to increase the number of bond pads. To increase the number of bond pads, the location of bond pads must be relocated from the tail edge to the back side ege of the slider. At new location, a new bonding process by the 1064 nanometer Nd-YAG laser with pulse widths at 30 millisecond is applied to replace the solder jet bonding process. The result shows that the laser bonding process is feasible with 1 laser point, 60 milliJoule of laser energy, 550 micrometre of laser diameter and 3 Newton of holding force. With these parameters, the bonding process is investigated for flaw at the bonding joint by using Scanning Electron Microscopy. The result shows that the slider is bonded with flawless joint and acceptable effects as the intermetallic compound is occurred.